Educating for biodiversity conservation in urban parks - Guerra Salcedo, Marisela de la Caridad; Morales Crespo , Carlos Manuel; Cruz Alonso , Suzel (Transformación, 2024)
This article is intended to propose a procedure for learning about biodiversity in urban parks, as a contribution for educating conservation of natural resources. The procedure was named “Diagnosis of biodiversity conservation status in urban parks”. It comprises for stages describing the physic, geographic, socio-historic, and cultural study of the park as well as a taxonomic inventory of species, its distribution, presence in Cuba, and menaces they are subjected to. This facilitates to carry out educative activities. The introduction of the procedure is thought of from an ethno-biological and interdisciplinary perspective for training students in biological, geographical, historical, cultural and ethnological procedures, seeking a holistic approach to environment. The effectiveness of the proposal was appraised by accounting the experience of a class at “Casino Campestre” park in Camagüey City.